Investigation into the event-activity dependence of ϒ(nS) relative production in proton-proton collisions at $$ \sqrt{s} $$ = 7 TeV - Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Ambrogi, F.; Bergauer, T.; Dragicevic, M.; Eroe, J.; Del Valle, A. Escalante; Flechl, M.; Fruehwirth, R.; Jeitler, M.; Krammer, N.; et al. (Springer Science and Business Media LLC, 2020)
AbstractThe ratios of the production cross sections between the excited ϒ(2S) and ϒ(3S) mesons and the ϒ(1S) ground state, detected via their decay into two muons, are studied as a function of the number of charged particles in the event. The data are from proton-proton collisions at$$ \sqrt{s} $$s= 7 TeV, corresponding to an integrated luminosity of 4.8 fb−1, collected with the CMS detector at the LHC. Evidence of a decrease in these ratios as a function of the particle multiplicity is observed, more pronounced at low transverse momentum$$ {p}_{\mathrm{T}}^{\upmu \upmu} $$pTμμ. For ϒ(nS) mesons with$$ {p}_{\mathrm{T}}^{\upmu \upmu} $$pTμμ>7 GeV, where most of the data were collected, the correlation with multiplicity is studied as a function of the underlying event transverse sphericity and the number of particles in a cone around the ϒ(nS) direction. The ratios are found to be multiplicity independent for jet-like events. The mean$$ {p}_{\mathrm{T}}^{\upmu \upmu} $$pTμμvalues for the ϒ(nS) states as a function of particle multiplicity are also measured and found to grow more steeply as their mass increases.
Keywords: B physic; Pbpb collisions; Quarkonium; QC770-798; Particle correlations and fluctuation; transverse momentum dependence; Particle correlations and uctuations; B physics; Physics, Particles & Fields; CROSS-SECTIONS; High Energy Physics - Experiment; Particle and Plasma Physics; Hadron-Hadron scattering (experiments); [PHYS.HEXP]Physics [physics]/High Energy Physics - Experiment [hep-ex]; Particle Physics Experiments; ground state; differential cross section: ratio; info:eu-repo/classification/ddc/530; Particle Correlations and Fluctuations; underlying event; Mathematical Physics; CMS; Physics; ddc:530; and fluctuations; Higgs physics; B physics; Hadron-Hadron scattering (experiments); Particle correlations; and fluctuations; Quarkonium; Pp collisions; Particle multiplicity; Pbpb collisions; CROSS-SECTIONS; Collectivity; Upsilon(2s); State; LHC; multiplicity: dependence; Experiment (hep-ex); Nuclear & Particles Physics; charged particle; Particle correlations and fluctuations; State; muon: pair production; transverse; Hadron-Hadron Scattering (Experiments); CERN LHC Coll; Upsilon(2s); GeV-cms; Physical Sciences; Atomic, Molecular, Nuclear, Particle and Plasma Physics; Physique des particules élémentaires; Particle physics; LHC; sphericity; B physics; Hadron-Hadron scattering (experiments); Particle correlations and fluctuations; Quarkonium; High energy physics; Experimental particle physics; LHC; CMS; Particle Physics Experiments; Physics; Vector boson scattering; Hadron-Hadron scattering (experiments); Supersymmetry; Higgs physics; Particle and resonance production; B physics; Particle correlations and fluctuations; Quarkonium; p p: scattering; [PHYS.HEXP] Physics [physics]/High Energy Physics - Experiment [hep-ex]; upsilon mesons: hadroproduction; transverse momentum: low; Particles & Fields; B physics; Hadron-Hadron scattering (experiments); Particle correlations and fluctuations; Quarkonium; Particle and resonance production; meson; charged particle: multiplicity; Nuclear and particle physics. Atomic energy. Radioactivity; muon; upsilon mesons: leptonic decay; Nuclear; High Energy Physics; High energy physics; ЭБ БГУ::ЕСТЕСТВЕННЫЕ И ТОЧНЫЕ НАУКИ::Физика; Quantum Physics; Science & Technology; Pp collisions; Particle correlations; Physics; LHC